2020
DOI: 10.1111/1440-1681.13263
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA LEF1‐AS1 is involved in the progression of retinoblastoma through regulating the Wnt/β‐catenin pathway

Abstract: The lymphoid enhancer binding factor 1 antisense RNA 1 (LEF1‐AS1) has been suggested to function as a tumour‐associated lncRNA in several types of human cancers, but there is no study to date about the role of LEF1‐AS1 in retinoblastoma. In our study, LEF1‐AS1 expression was increased in retinoblastoma tissues and cell lines compared with paired adjacent normal tissues and the retinal pigment epithelial cell line, respectively. Meanwhile, we found that patients with retinoblastoma with IIRC D‐E or undifferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Several studies have demonstrated that lncRNAs exert pivotal functions in retinoblastoma via acting as tumor suppressors or oncogenes. [10][11][12] High expression in hepatocellular carcinoma (HEIH), also known as hepatocellular carcinoma up-regulated EZH2-associated long non-coding RNA, is a recently identified intergenic lncRNA located in chromosome chr5:-180256954-180258618. HEIH was firstly characterized to be overexpressed in HBV-related hepatocellular carcinoma tissues compared with paired peritumoral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that lncRNAs exert pivotal functions in retinoblastoma via acting as tumor suppressors or oncogenes. [10][11][12] High expression in hepatocellular carcinoma (HEIH), also known as hepatocellular carcinoma up-regulated EZH2-associated long non-coding RNA, is a recently identified intergenic lncRNA located in chromosome chr5:-180256954-180258618. HEIH was firstly characterized to be overexpressed in HBV-related hepatocellular carcinoma tissues compared with paired peritumoral tissues.…”
Section: Introductionmentioning
confidence: 99%
“… 23 In glioblastoma tissues, LEF1‐AS1 was highly expressed and elevated cell malignant behaviors by sponging miR‐543 to upregulate the expression of EN2. 24 LEF1‐AS1 was also overexpressed and functioned as an oncogene in hepatocellular carcinoma, 25 ovarian cancer, 26 retinoblastoma, 27 osteosarcoma, 28 esophageal squamous cell carcinoma, 29 non‐small‐cell lung cancer, 30 oral squamous cell carcinoma, 31 and prostate cancer, 32 while in myeloid malignancy, LEF1‐AS1 was downregulated and served as a tumor suppressor lncRNA. 33 LINC01224 in our signature has also been used to establish a risk model for predicting BC patients’ prognosis in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Li and his colleagues pointed out that LEF1-AS1 promotes the metastasis of prostatic carcinoma through the Wnt/β-catenin pathway (Li W. et al, 2020). Similarly, He et al (He and Qin, 2020) found that silent LEF1-AS1 inhibited the biological function of retinoblastoma cells by inhibiting the expressions of β-catenin and LEF1. The Wnt/β-catenin pathway has also been confirmed to be involved in the occurrence and progression of osteosarcoma (Lu et al, 2020) and colorectal cancer (Qi et al, 2021).…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 97%
“…Certain studies reported a significant overexpression of LEF1-AS1 in osteosarcoma, prostate cancer, and retinoblastoma (Liu et al, 2019;Li W. et al, 2020;He and Qin, 2020;Lu et al, 2020). He et al pointed out that high expression of LEF1-AS1 predicted poor prognosis in retinoblastoma.…”
Section: Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation